Does Patient Age Impact In-Office Tooth Bleaching Outcomes? A Parallel Clinical Trial - Martins, J L; Araújo, I S; Rabelo, J F; Soares, C J; Faria-E-Silva, A L; Loguercio, A D; Filho, Pcfs; Carlo, H L; da Silva, G R (Operative dentistry, 2025)
To assess the influence of patient age on tooth sensitivity, bleaching effectiveness, and the self-perception and psychosocial impact of dental esthetics following in-office tooth bleaching with 35% hydrogen peroxide. This parallel study categorized 56 subjects by age into early adulthood (18-25 years) and middle-aged (40-65 years) groups. The bleaching agent was applied in a single 45-minute session, spanning two bleaching sessions at a 1-week interval. Bleaching effectiveness assessment used upper incisors and canines. A shade guide (VITA Bleachedguide 3D-MASTER) and a portable spectrophotometer evaluated color changes. A visual analog scale and verbal rating scale recorded tooth sensitivity during and up to 48 hours after the bleaching procedure. The Psychosocial Impact of Dental Aesthetics Questionnaire measured the self-perception and psychosocial impact of the bleaching protocol. Student t-test, Fisher exact test, Mann-Whitney, multivariate analysis of variance, chi-square, two-way repeated measures analysis of variance, and the Wilcoxon test (α=0.05) verified the data. Early adulthood subjects demonstrated a significant increase (17%) in the risk of tooth sensitivity (p=0.038), and the highest pain levels occurred 1 hour after the bleaching session (p<0.01). Nonetheless, early adulthood subjects showed improved bleaching effects 30 days after the procedure when compared to the middle-aged subjects, even though the overall perception of the psychosocial impact of dental esthetics was more evident in middle-aged subjects. Patient age influenced in-office bleaching outcomes. Both age groups reported esthetic satisfaction, but early adulthood subjects (18-25 years) experienced a more substantial whitening effect, greater dentin sensitivity, and higher psychological impact. Conversely, middle-aged subjects (40-65 years) had a better overall perception of the psychosocial impact of dental esthetics.